2017
DOI: 10.1002/ece3.3220
|View full text |Cite
|
Sign up to set email alerts
|

Utility of DNA barcoding to identify rare endemic vascular plant species in Trinidad

Abstract: The islands of the Caribbean are considered to be a “biodiversity hotspot.” Collectively, a high level of endemism for several plant groups has been reported for this region. Biodiversity conservation should, in part, be informed by taxonomy, population status, and distribution of flora. One taxonomic impediment to species inventory and management is correct identification as conventional morphology‐based assessment is subject to several caveats. DNA barcoding can be a useful tool to quickly and accurately ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 78 publications
1
13
1
Order By: Relevance
“…Although the average values were not much different between plastomic and matK data, the minimum value of matK (0.005) was much lower than that of the plastome (0.012). While some previous studies showed that matK was not able to identify all species in some close taxonomic groups [65,66], our result suggests that the entire cp genome could do better than matK in identifying closely related species. The chloroplast genome was proposed to be used as meta-barcode by some previous studies [61][62][63][64].…”
Section: Phylogenetic and Species Resolution Analysescontrasting
confidence: 92%
“…Although the average values were not much different between plastomic and matK data, the minimum value of matK (0.005) was much lower than that of the plastome (0.012). While some previous studies showed that matK was not able to identify all species in some close taxonomic groups [65,66], our result suggests that the entire cp genome could do better than matK in identifying closely related species. The chloroplast genome was proposed to be used as meta-barcode by some previous studies [61][62][63][64].…”
Section: Phylogenetic and Species Resolution Analysescontrasting
confidence: 92%
“…[3]), protecting endangered species (e.g. [4]), controlling agricultural pests (e.g. [5]), and identifying diseases (e.g.…”
Section: María P Martín 1☯ Pablo P Danië Ls 2☯ David Erickson 3mentioning
confidence: 99%
“…Many papers on barcoding methodology choose to focus on issues other than the species concept, e.g., on the quality of primer annealing to DNA, the different strategies for matching an unknown query sequence with sequences in a reference database, the use of BLAST scores, etc. [4], but the species definition lies at the heart of DNA barcoding. For general reference sets of sequence data, however, investigators often turn to GenBank [9], where non-experts may have submitted the species annotations (e.g., [10]).…”
Section: María P Martín 1☯ Pablo P Danië Ls 2☯ David Erickson 3mentioning
confidence: 99%
“…The results of the present study show a successful identification of Silene schimperiana on the species and genus levels. The success of species identification using DNA barcoding is contributing to the availability of nucleotide data of the corresponding taxa in the DNA sequences database [37]. However, additional experiments with other markers to entirely identify the plant more accurately are required.…”
Section: Identification Of Silene Schimperiana By Dna Barcode Analysismentioning
confidence: 99%